Do Vale do Bekaa para a margem do Rio Madeira: família Hijazi (1950-1980) - Hijazi, Youssef Cavalcante, Youssef Cavalcante (2024)
This master’s dissertation focuses on the immigration of the Hijazi family from Lebanon to Brazil and their adaptation to a new reality, that is, the change of homeland and the adoption of new customs. Leaving the Bekaa Valley in 1955, the first Hijazi, upon crossing the Atlantic and landing on Brazilian soil, created the necessary bonds to settle down and began to advocate for the arrival of other family members. The Hijazis' destination was the city of Porto Velho, a city that welcomed them and where they were influenced by the local culture, while the newly arrived Lebanese also exerted cultural influence on the local community. The research problem is: how did the Hijazi family adapt to living in Porto Velho, RO, after immigrating to Brazil? Was there cultural hybridity? The general objective of this study is to investigate how the Hijazi family rebuilt their lives and culture in Brazil from the 1950s onwards. To meet the proposed objectives, the research focused on the period from 1950 to 1980, when the family patriarchs' migration ended. The methodology used was Oral History, as it allows us to learn about the experiences and historical trajectories of immigrants based on their memories, fostering an important reconstruction of history and identity. The research sources used were photographs from the Hijazi family's personal archive, such as photos of family members, personal documents, passports, immigration records, various commercial enterprises (drugstore, restaurant and snack bar) and letters exchanged between family members. In addition, interviews were conducted to collect important information about the trajectories and life stages of the immigrant family members. It concludes that Lebanese immigrants in Brazil and Porto Velho constructed a cultural hybridism, which can be identified in the relations between Brazilians and Lebanese, Christianity and Islam, and in the cuisine of Lebanese immigrants who settled in Brazil.